Curriculum, syllabus design, and equity a primer and model - Luke, Allan; Woods, Annette; Weir, Katie; T&F eBooks (New York, N.Y. : Routledge, 2013)
"Curriculum scholars and teachers working for social justice and equity have been caught up in acrimonious and polarizing political debates over content, ideology, and disciplinary knowledge. At the forefront in cutting through these debates and addressing the practical questions involved, this book is distinctive in looking to the technical form of the curriculum rather than its content for solutions. The editors and contributors, all leading international scholars, advance a unified, principled approach to the design of curriculum and syllabus documents that aims for high quality/high equity educational outcomes and enhances teacher professionalism with appropriate system prescription. Stressing local curriculum development capacity and teacher professional responses to specific community and student contexts, this useful, practical primer introduces and unpacks definitions of curriculum, syllabus, the school subject, and informed professionalism; presents key principles of design; discusses a range of approaches; and offers clear, realistic guidelines for the tasks of writing curriculum documents and designing official syllabi and professional development programs at system and school levels. Providing a foundational structure for syllabus design work, Curriculum, Syllabus Design, and Equity is relevant for teachers, teacher educators, and curriculum policy workers everywhere who are engaged in the real work of curriculum writing and implementation"--
1. Introduction : the practical problem of curriculum making / Allan Luke -- 2. Curriculum design, equity and the technical form of the curriculum / Allan Luke, Annette Woods and Katie Weir -- 3. School subjects and academic disciplines : the differences / Zongyi Deng -- 4. Curriculum policy guidelines : context, structures and functions / F. Michael Connelly and Gerry Connelly -- 5. The technological solution to reading education : a century of frustration / Patrick Shannon -- 6. Sustaining teacher professionalism in the context of standards referenced assessment reform / Val Klenowski -- 7. Social justice visions and curriculum realities in the early years of education / Susan Grieshaber -- 8. Curricular conversations : literacy teaching and learning in the middle years / Donna E. Alvermann and James Marshall -- 9. Improving secondary schools / Ben Levin -- 10. Generalizing across borders : policy and the limits of educational science / Allan Luke.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Curriculum planning -- Methodology; Educational equalization; Social justice -- Study and teaching; Electronic books